Clinicopathologic study of pelvic lesions managed by surgeons in a medical college in Kolkata in the last 2 years - Bhattacharyya Nirmal; Mallick Mamata; Roy Himansu; Das Mrinal; Gautam Dibyendu (Wolters Kluwer Medknow Publications, 2008)
The pelvic cavity is a basin-like space in the lowermost part of the abdomen where various neoplastic and non neoplastic lesions can occur involving its contents. When the nature of lesions are not clearly gynecological, patients are managed by surgeons. Our study aims to asses the clinicopathologic analysis of neoplastic lesions of the pelvic cavity managed by surgeons particularly over a period of 2 years. Out of 162 total lesions, 102 cases were non neoplastic, such as appendicular lump, Tubo-ovarian (TO) mass, hematoma and 60 cases were neoplastic. Among the 60 cases of neoplastic lesions, 40 cases were benign comprised of twisted ovarian cyst, broad-ligament fibroid, and neurofibroma and 20 cases were malignant comprised of colorectal carcinoma, ovarian carcinoma, liposarcoma, Primitive nurectodermal tumor (PNET), seminoma, and lymphnode metastasis. The lesions in such closed, difficult to approach areas throws clinicians into a diagnostic dilemma during both the preoperative and intraoperative period. Even pathologists cannot ascertain some diagnosis without the help of immunohistochemistry. So, to adopt early and concise management protocol, there should be more such studies in different institutions that are currently lacking in world literature.